The prices of residential land in German counties - Stefanie Braun; Gabriel S. Lee (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2020)
We estimate changes in the value and price of residential land for 379 German counties ("Landkreise") from 2014 to 2017 using a total of 42,685 observations. We use the two-step residual method that decomposes the value of a home into the value of the structure and land value. Despite the short time series, we show that the price of residential land has become relatively more expensive in the majority of German counties. More specifically, we show that the cumulative change in land values varies between 9% and 171% (excluding Berlin with exorbitant high increases of 668% and Saarland with a decrease of 18%) from 2014 to 2017. On average, the home values increased by 30% and 15% for West and East Germany respectively, whereas the land values increased by 108% and 91% for West and East Germany. Our findings imply that cycles in the German land values are more likely to affect the evolution of house prices more in the future than they did in the past. Moreover, our estimated land prices vary significantly to the current land price valuation by one of the German state governments (Hessen).
Keywords: R0; R11; R14; R21; R31; 330; German Land prices; Land values; German Housing prices; Housing values; Construction costs; Replacement costs